Reporting incidental findings from non-biological assessments in human subject research - Pingitore, Alyssa; Mack, Ashley; Zhang, Justin; Devine, Eric G; Doerr, Jackson; Denneen, Caroline (Research ethics review, 2022)
Incidental findings in research with human participants may have implications for a person’s present health or future health outcomes. Current guidelines focus on methods for handling and reporting incidental findings from biological test data but incidental findings might also arise from non-biological tests. This article presents three examples in which the results from non-biological test data can be predictive of future disease and should be disclosed to research participants. It is intended to increase awareness and facilitate further discussion about the reporting of incidental findings from non-biological data.